Thiosemicarbazone derivatives synthesis as a potent alternative to skin disease inhibitor : experimental and theoretical approach - Muhammad Qusyairi Jori Roslan (Kulliyyah of Science, International Islamic UniversityMalaysia, 2020)
Skin disease inhibitor has been recognized as one of the most demanding antibiotics in the cosmetic industries due to the increment annually. Recently heterocyclic and thiosemicarbazide compounds have been shown to be excellent skin inhibitor due to their ability to inhibit bacteria, fungus, and enzyme tyrosinase. Therefore, in this study, we have produced 5 compounds from these two bio-active fragments (thiosemicarbazide and heterocyclic compound) in one molecular architecture approach elimination process. All the ynthesized compounds were analysed using determination and spectroscopic method such as elemental analysis, melting point and UV-Visible, FTIR, and NMR respectively. The synthesized compounds were subsequently tested for microbial and tyrosinase enzyme assay activity and discovered that 2-Apt-2AOH was the most promising inhibitor against both activities. In microbial activity 2-Apt-2-AOH was successful to inhibit 17 ± 1.53 mm, 13 ± 0.58 mm, and 29 ± 0.58 mm for Staphylococcus aureus, Staphylococcus epidermidis, and Candida albicans respectively at concentration 10 µg/ml while for concentration 20µg/ml, the respective compound inhibited 18 ± 1.13 mm, 19 ± 0.58 mm, and 30 ± 0.58 mm accordingly. Enzyme inhibitor test was depicted that 2-Apt-2-AOH profile the lowest energy value in which contributed to high binding affinity and demonstrated the best enzyme activity inhibitor comparable to other compounds. From the Michaelis-Menten graph, it was discovered that Km value for respective compound was at 0.04 µg/ml. From the value, it indicates that 2-Apt-2-AOH has well binding interaction with the enzyme. Double reciprocal from Michaelis-Menten graph led to Lineweaver-Burk plot which in this plot explained the type of inhibitor and 2-Apt-2-AOH was classified as non-competitive inhibitor. Computational chemistry was employed to enhance the understanding of physico-chemical behavior and interaction of synthesized compound with protein receptor. COSMO-RS, RDG-NCI plot, MEP and Molecular Docking were applied in this study as COSMO-RS provide the chemical behavior of the synthesized compound with solvent while RDG-NCI plot study on the non-covalent interaction by using reduced gradient density. On the other hand, MEP was used to identify the active site of a molecule in which involve to do the interaction with protein. Extended study respected to the synthesized compound and protein interactions was explained by Molecular Docking approach. In this section, the several kinds interaction involved of bonding such as hydrogen bond, π-π stacking interaction and Van der Waals were shown.